MANAJEMEN OPERASIONAL PAKET WISATA CITY TOUR SURAKARTA DI PT. KIRANA SURYA GEMILANG YOGYAKARTA Yogyakarta ( Studi Kasus Rombongan Ikatan Wanita Bank ) - , EDWIN HASTAWI ATMAJA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tourism is one reliable sector in indonesia. Proved by the great contribution for being the second place of the biggest source foreign exchange after oil and gas. This final assignment report is to study about the operational management city tour package. This research is purposed to specify in details ofc how is the operational management of city tour package in Kirana Tour Yogyakarta. The writer used the cualitative method on data collection that obtain from many data collection technic. So with live research the writer could analyze the formulate problem to be the problem summary of this research. And the value of this final assignment writting is, writer know that the operasional management of city tour package could be seen from how the way the answer or react to the consument, the counting technic of basic cost, tour perform and the evaluation after it finish who could not be escape from the team work operational management that used by Kirana Tour are success, so that the consument who used service are satisfied. And with good operational management of tour package, the consumentâs interest to use Kirana Tourâs service on the tour service would increase.